Do "Any Willing Provider" and "Freedom of Choice" Laws Affect HMO Market Share? - Michael A. Morrisey; Robert L. Ohsfeldt (SAGE Publishing, 2003)
This study examines the effects of "any willing provider" (AWP) and "freedom of choice" (FOC) laws on the market share of health maintenance organizations (HMOs) in metropolitan statistical areas over the period 1989-95. We use pooled cross-section time-series regression techniques with year and state fixed effects. HMO market share is hypothesized to be a function of state laws, market characteristics, and state preference for managed care regulation. AWP and FOC laws are characterized by three alternative measures of regulatory intensity. The results suggest that FOC laws have a greater impact on market share than do AWP laws. More comprehensive regulation has a bigger impact than less encompassing laws, and laws limiting selective contracting with physicians are more effective in reducing HMO market share than are laws covering hospitals or pharmacies.